The Effects of Dietary ω -3 and ω -6 Fatty Acids on Nutrient Utilization and Growth Performance in Sahiwal Heifers - Kumar, Sushil; Sihag, Sajjan; Sihag, Zile Singh; Patil, C S; Dhaka, Surender Singh; Pandey, Anand Kumar (Indian Journal of Animal Nutrition, 2020)
The study was conducted to evaluate the effect of dietary supplementation with omega-3 and omega-6 rich oil on nutrient utilization, growth performance and pubertal age in Sahiwal heifers. Eighteen healthy sahiwal heifers of average 18.33±1.14 month’s age and 194±4.16 kg body weights were randomly assigned to 3 treatment groups viz T1, T2 & T3 with 6 animals in each. Heifers were individually fed as per ICAR (2013) diets of chopped wheat straw, green fodder and concentrate mixture. The concentrate mixtures fed to the heifers under treatment group T2 and T3 were supplemented with omega-6 fatty acid rich soybean oil and omega-3 fatty acid rich linseed oils @ 3.5 percent, respectively. To make the rations iso-caloric, palm oil @ 3.5 percent was supplemented in the concentrate mixture of heifers in control group (T1). All the concentrate mixtures were isonitrogenous. Daily DMI was significantly (P